Personality characteristics recidivists (Journal of actual problems of jurisprudence, 2018)
This article discusses the specific features of the personality of recidivists. When writing the socio-demographic and psychological characteristics are based on the opinions of scientists from different fields of science. Also disclosed the commitment and active dissemination by recidivists criminal subcultures and the negative impact of criminal traditions for socially unstable persons (especially for youth) and persons prone to deviant behavior.An attempt was made to formulate proposals for the improvement of preventive measures penitentiary relapse.Key words: criminal recidivist, the identity of the offender, subculture, criminal environment, deviant behavior,penitentiary relapse.